Was unofficial dollarisation/euroisation an amplifier of the 'Great Recession' of 2007-09 in emerging economies - Livia Chiţu (European Central Bank (ECB), 2012)
This paper investigates whether, and if so why, the recent `Great Recession' was more severe in unofficially dollarised/euroised economies than in other economies. To that end, the paper builds on a novel dataset on unofficial dollarisation/euroisation to test whether the latter was a determinant of the extent of the growth collapse in 2007-09 in a cross-section of around 60 emerging market economies. Both OLS and Bayesian model averaging estimates suggest that unofficial dollarisation/euroisation was an important contributor to the severity of the crisis, once other of its well-established determinants are taken into account, including fast pre-crisis credit growth, current account deficits, trade and financial openness, market regulation, international openness of the banking sector and GDP per capita. Moreover, the adverse impact of unofficial dollarisation/euroisation is found to have been transmitted through the main channels traditionally highlighted in the literature, i.e. currency mismatches, reduced monetary policy autonomy and limited lender of last resort ability, all of which became more binding constraints in the midst of the crisis. The results help to shed light on the long-standing debate regarding the conduct of monetary policy in unofficially dollarised/euroised economies in crisis times.
Keywords: F30; G01; G21; 330; Bayesian model averaging; emerging economies; foreign currency lending; Great Recession; Unofficial dollarisation/euroisation